2012
DOI: 10.1007/s12199-012-0304-8
|View full text |Cite
|
Sign up to set email alerts
|

Reference value and annual trend of white blood cell counts among adult Japanese population

Abstract: Objectives This study was initiated to establish the reference values (the 95 % lower limit in particular) for white blood cell (WBC) counts in peripheral blood of general Japanese population. Additional attempts were made to examine whether the reference range had changed in the past 100 years, and which factors had induced such change in WBC counts. 3 WBCs/mm 3 (after rounding of the figure) was identified as the 95 % lower limit of the reference value for the population. No clear age dependency was detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
1
10
0
1
Order By: Relevance
“…Normal values may vary depending on the assay used by laboratory. Moreover, among factors influencing WBC are: infections, autoimmunological disorders, splenomegaly and splenectomy, but also age (complex dependence, conflicting results) [2,3], medications [3,4], body weight (positive correlation)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal values may vary depending on the assay used by laboratory. Moreover, among factors influencing WBC are: infections, autoimmunological disorders, splenomegaly and splenectomy, but also age (complex dependence, conflicting results) [2,3], medications [3,4], body weight (positive correlation)…”
Section: Introductionmentioning
confidence: 99%
“…Archives of Psychiatry and Psychotherapy, 2017; 3: 16-26 [3,5,6], smoking (positive correlation) [2,7], alcohol consumption (inverse association) [3,8], exposure to benzene (leukocytopenia) [2]. Sun et al concluded that subnormal WBC counts (<3.9 × 10 9 cells/L), which rather exclude even lowgrade systemic inflammation, are related to the lower prevalence of metabolic syndrome and the lowest incidence of metabolic syndrome during a 5-year follow-up period among healthy population than WBC counts within reference range [9].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of leukocytopenia <4,000/ μ l has been reported to be 5.5% in a general population of 130,431 Japanese men, which was about half of the rate in the present alcoholic population (Sakuragi et al., ). Alcohol drinking and low BMI were associated with a decrease of leukocyte counts and cigarette smoking was associated with an increase of leukocyte counts in Japanese men who participated in health checkups (Mochizuki et al., ; Nakanishi et al., ), consistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 76%
“…In Budget Plan 2, the non-statutory items with a selection rate >80%, with the exception of serum creatinine, were white blood cell count (92%), uric acid (89%), and fecal occult blood reaction (81%). White blood cell count can be used for the detection of leukemia and hematologic diseases 24) , and is also useful for the risk and aptitude assessments in pathogen-related businesses and the hospitality industry, as well as to provide health guidance to smokers with an increased white blood cell count 25) . Uric acid with poorly controlled hyperuricemia can cause gout attacks, thereby affecting work productivity by unexpected absences and pain.…”
Section: Discussionmentioning
confidence: 99%